Laser 904 nm action on bone repair in rats with osteoporosis - Pires-Oliveira, D. A. A.; Oliveira, R. F.; Amadei, S. U.; Pacheco-Soares, C.; Rocha, R. F. [UNESP] (Springer London Ltd, 2010)
The aim of the present study was to determine the action of AsGA laser irradiation on bone repair in the tibia of osteopenic rats. The animals were randomly divided into eight experimental groups according to the presence of ovarian hormone (sham group) or the absence of the hormone (OVX group), as well as being irradiated or non-irradiated. Low-level 904-nm laser (50 mJ/cm(2)) accelerated the repair process of osteopenic fractures, especially in the initial phase of bone regeneration.Introduction The development of new techniques to speed the process of bone repair has provided significant advances in the treatment of fractures. Some attention recently focused on the effects of biostimulation on bone.Methods Forty-eight adult rats were randomly divided into eight experimental groups (six animals in each group) according to the presence of ovarian hormone (sham group) or absence of the hormone (ovariectomized (OVX) group) as well as being irradiated or non-irradiated. For the application of low-level laser therapy, the animals were anesthetized with one third of the dose sufficient to immobilize the animal and irradiated with AsGa laser (904 nm, 50 mJ/cm(2) for 2s, point form and in contact). The control animals received the same type of manipulation as the irradiated animals, but with the laser turned off. Half of the animals were killed 7 days following the confection of the bone defect, and the other half were killed 21 days after the surgery. After complete demineralization, the tibias were cut cross-sectionally in the central region of the bone defect and embedded in paraffin blocks. The blocks were then cut in semi-seriated slices and stained with hematoxylin and eosin.Results There was new bone formation in the animals in the OVX group with laser treatment killed after 7 days (p<0.001). The lowest percentage of bone formation was observed in the OVX without laser killed after 7 days (p>0.05). All animals killed after 21 days exhibited linear closure of the lesion.Conclusion Low-level 904-nm laser (50 mJ/cm(2)) accelerated the repair process of osteopenic fractures, especially in the initial phase of bone regeneration.
Keywords: Bone regeneration; Low-level laser therapy; Osteoporosis; Photobiomodulation